2022
DOI: 10.3389/fnagi.2022.863379
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Limb Rehabilitation Therapy After Post-stroke Motor Recovery

Abstract: Stroke, including hemorrhagic and ischemic stroke, refers to the blood supply disorder in the local brain tissue for various reasons (aneurysm, occlusion, etc.). It leads to regional brain circulation imbalance, neurological complications, limb motor dysfunction, aphasia, and depression. As the second-leading cause of death worldwide, stroke poses a significant threat to human life characterized by high mortality, disability, and recurrence. Therefore, the clinician has to care about the symptoms of stroke pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 112 publications
0
7
0
1
Order By: Relevance
“…Motor dysfunction is one of the most common complications following stroke, which manifests as numbness and weakness of the limbs and even paralysis or spasms [ 13 , 52 ]. Motor dysfunction can seriously affect the quality of life and social participation of stroke patients.…”
Section: The Role Of Music Therapy In the Rehabilitation Poststrokementioning
confidence: 99%
See 1 more Smart Citation
“…Motor dysfunction is one of the most common complications following stroke, which manifests as numbness and weakness of the limbs and even paralysis or spasms [ 13 , 52 ]. Motor dysfunction can seriously affect the quality of life and social participation of stroke patients.…”
Section: The Role Of Music Therapy In the Rehabilitation Poststrokementioning
confidence: 99%
“…Music therapy is a systematic treatment method that utilizes music elements as an intervention to improve patients' neurological function and mood status [ 11 , 12 ]. Many studies have applied music therapy during rehabilitation of stroke, which has led to the achievement of a good effect [ 13 , 14 ]. Due to its safety, it is low cost, convenient, simple, and easy to implement.…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics, 55%−75% of poststroke patients suffer from upper limb (UL) motor impairments (2). Despite receiving intensive rehabilitative therapies, many patients post-stroke retained motor dysfunction at variable degrees (3)(4)(5), which decreased health-related quality of life (6). Recently, many studies have suggested that repetitive transcranial magnetic stimulation (rTMS) may be a promising therapy for promoting recovery of the upper limb after stroke (7)(8)(9)(10), possibly through modulating cortical excitability and inducing neural plasticity (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring music in its various forms can be a vital part of holistic nurses' efforts to rehabilitate and comfort patients dealing with adversities such as stroke. 25,26 Moreover, like love and sorrow, music has the power to change the way the patient perceives the world; in this way, music and mood are linked. The use of guided imagery music serves as an example in this regard.…”
Section: Musicmentioning
confidence: 99%